ANALISIS PENENTUAN SUKU BUNGA DEPOSITO PADA BANK UMUM DI INDONESIA PERIODE TAHUN 2004 2009 - ME, ASTRI FEIZATY (Jurnal Ekonomi Daerah (JEDA), 2013)
This Research was aimed to investigate the shaping of deposit rate interest in public banks in indonesia in 2004-2009 period and how big the impact of the rate of Bank Indonesia, active circulation, inflation and rupiahs exchange rate on the deposit rate of interest in public bank in Indonesia. This research used time series secondary data. The secondary data which was used was monthly data in 2004-2009 which was gotten from the yearly report of Bank Indonesia, economy statistic of Indonesians Finance, Literature study, as well as other banking data. A descriptive method was used in this research. To analyze the data in ths research, the tool of analysis which were test for normality and classic assumption test which consisted of multicollinearity test and autocorrelation test. The analysis model which was used was multiple regression analysis model. he finding of the research showed that the rate of Bank Indonesia, active circulation, inflation and the determining of rupiahs exchange rate on the deposit rate of interest in a month was 95%, while the rest 5% was the impact of other factors which was not investigated in this research. Partially, the rate of Bank Indonesia brought positive impact on the determining of deposit rate of interest in 1 month for 78,15%. The active circulation brought negative impact on the deposit rate of interest in1 month for 37,82%. The inflation brought positive impact on the deposit rate of interest in 1 month for 24,50%. Rupiahs exchange rate brought positive impact the deposit rate of interest in 1 month for 43,03%. Key word : deposit rate of interest, the rate of Bank Indonesia, active circulation, inflation, Rupiahs exchange rate